Mobile user behavior analysis system and applications based on big data - Hongxun GU; Ke YANG (Dianxin kexue)
Based on Hadoop’s architecture，this system collects and analyzes the telecom operator network’s data to build up user behavior model for effective exploration of big data applications.The whole process was discussed，including data collection，system design，implementation and application cases.